Development of the Steinberg Method Using Canva Media in the Early Reading Skills of Elementary School Students on Science Concepts - Hasan, Amin; Leksono, Suroso Mukti; Nulhakim, Lukman (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study aimed to: (1) identify the profile of students' initial reading learning, (2) design the Steinberg method assisted by Canva Media for initial reading learning, (3) determine students' responses to learning media using Canva Media, and (4) determine teachers' responses to the initial reading learning model through the Steinberg method assisted by Canva Media. The research method used was Research and Development (RD) based on the Dick, Carey, and Carey framework. The research results indicate that: (1) the development of the early reading model through the Steinberg method and Canva Media was carried out through 10 stages, namely: needs identification, development, learner and context analysis, breakdown of competency objectives, instrument development, learning strategies, selection of teaching materials, formative evaluation, revision, and summative evaluation. (2) Students' responses to the early reading learning media using Canva were mostly positive. (3) Teachers' responses to the early reading learning product using the Steinberg method assisted by Canva were deemed appropriate and suitable for use in early reading instruction at elementary schools. This study concludes that the use of the Steinberg method-based early reading learning model using Canva as a medium has proven effective, is well-liked by students, and is deemed appropriate by teachers for implementation in elementary schools, allowing for further field trials.